« Self Cartography », une narration autour du monde - Adèle Davanture; Daniel Derivois (M@ppemonde)
The present article proposes to use the geographical map as a tool to narrate the psychological suffering caused by the migration. Based on the development of a specific methodology named “Self Cartography” in the field of clinical psychology, the article will present the creation process of this method and its illustration by several clinical cases.